Psikoedukasi Dampak Perilaku Perundungan Pada Remaja Di SMA Negeri 1 Sukamulia - Nurmaulia Khotmi; Hartiani Hartiani; Elisa Sulistia Fitri (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Bullying behavior often occurs in all circles and all institutions, both government and private, including in the world of education, namely the school environment, the perpetrators and victims are teachers or students. Bullying is any physical violence or psychological violence that is carried out repeatedly due to the imbalance of power relations. The purpose of the psychoeducational activity is to provide information to teachers and students regarding the impacts caused by bullying behavior. Psychoeducational activities are carried out by means of face-to-face seminars at the SMAN 1 Sukamulia Musholla. The method in psychoeducational activities is action research or also called Action Research. Action Research consists of four processes starting from determining the problem, preparing an activity plan, implementing activities and finally conducting an evaluation related to the objectives of the educational activities carried out. The implementation process begins with the presentation of material, questions and answers, and sharing experiences related to bullying behavior experienced by students or adolescents.